Pengaruh Leverage, Ukuran Perusahaan, Pertumbuhan terhadap Profitabilitas Perusahaan (Sub sektor makanan & minuman) - Leppang, Irmawati; Torano, Nety; Sapari, Lili Sarce Joi (Innovative: Journal Of Social Science Research, 2024)
The aim of this research is to empirically test that leverage, sales growth and company size influence profitability simultaneously or partially. The data analysis technique uses multiple linear regression, with a sample of 12 food and beverage sub-sector companies listed on the IDX. Partial research results: H1: there is no influence of the leverage variable (X1) on the profitability variable (Y), so hypothesis H1 is rejected; H2: there is an influence of the sales growth variable (X2) on the profitability variable (Y), so hypothesis H2 is accepted; H3: there is an influence of the company size variable (X3) on the profitability variable (Y), so hypothesis H3 is accepted. Simultaneously, it can be interpreted that the variables leverage (X1), sales growth (X2) and company size (X3) together influence the profitability variable (Y). Meanwhile, the determination test provides information about the coefficient of determination value, namely the contribution or influence of variables X1,